Viral Performance : Contagious Theaters from Modernism to the Digital Age - Felton-Dansky, Miriam (Book collections on Project MUSE., 2018)
"Digital culture has occasioned a seismic shift in the discourse around contagion, transmission, and viral circulation. Yet theater, in the cultural imagination, has always been contagious. Viral Performance proposes the concept of the viral as an essential means of understanding socially engaged and transmedial performance practices since the mid-twentieth century. Its chapters rethink the Living Theatre's Artaudian revolution through the lens of affect theory, bring fresh attention to General Idea's media-savvy performances of the 1970s, explore the digital-age provocations of Franco and Eva Mattes and Critical Art Ensemble, and survey the dramaturgies and political stakes of global theatrical networks. Viral performance practices testify to the age-old-and ever renewed-instinct that when people gather, something spreads. Performance, an art form requiring and relying on live contact, renders such spreading visible, raises its stakes, and encodes it in theatrical form. The artists explored here rarely disseminate their ideas or gestures as directly as a viral marketer or a political movement would; rather, they undermine simplified forms of contagion while holding dialogue with the philosophical and popular discourses, old and new, that have surrounded viral culture. Viral Performance argues that the concept of the viral is historically deeper than immediate associations with the contemporary digital landscape might suggest, and far more intimately linked to live performance"--Provided by publisher